Adaptation and validation of the Portuguese version of Basic Psychological Needs Exercise Scale (BPNESp) to the sport domain and invariance across football and swimming - Monteiro, Diogo (2016)
The purpose of this study was to adapt and validate the Basic Psychological Needs Exercise Scale (BPNESp) to the sport domain, and to measure model invariance across football and swimming. Athletes (n=1382; 623 football, 759 swimming) with an average age of 18.77±SD 7.04 years participated in this study. Results supported the suitability of both the first and second order models, showing that the model was well adjusted to the data. In addition, the model showed the discriminant and convergent validity and composite reliability of the factors, and was invariant between football and swimming (ΔCFI≤.01).